The Influence Of Brand Characteristics And Emotional Branding On Purchasing Decisions At Coffee Shop Bengkulu - Ferdian Fachrie Hero Putra; Anzori Anzori; Eska Prima Monique Damarsiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
A coffee shop is a place that serves food and drinks, but mainly sells coffee. Generally, what is called a coffee shop is a coffee shop whose place is attractively designed and provides many coffee menus. The purpose of this study was to determine the effect of brand characteristics and emotional branding on purchasing decisions at Bengkulu coffee shops. In this study, the data used is quantitative data, namely data obtained from distributing questionnaires to service users at Coffee Shop Bengkulu. In this study the data used is quantitative data, namely data obtained from distributing questionnaires to consumers at Coffee Shop Bengkulu. Based on the results of the study, there is an influence of brand characteristics (X1) on purchasing decisions (Y) Coffee Shop Janji Jiwa with a tsig value < α (0.000 < 0.05) and a tcount> ttable value (5.749> 1.68195) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X1 has a positive effect on purchasing decisions (Y). There is an effect of emotional branding (X2) on purchasing decisions (Y) Coffee Shop Janji Jiwa with a tsig value < α (0.000 < 0.05) and a tcount> ttable value (4.346> 1.68195) thus Ho is rejected and Ha is accepted. From the significance value obtained that the X2 variable has a positive effect on purchasing decisions (Y).